Accuracy of surface registration in cranial electromagnetic navigation. Issue 2 (23rd April 2018) - Freysinger, Annette Runge; Steinbichler, Teresa; Giotakis, Aristeidis; Schartinger, Volker; Hörmann, Romed; Riechelmann, Herbert; Freysinger, Wolfgang
No abstract available